GIS For Local Authorities - Buyong, Taher (Fakulti Ukur dan Harta Tanah, 1995)
In the advent of computer technology, GIS has been rapidly adopted by many organizations as an effective tool for managing,organizing, and analyzing spatially related data. Local authorities who are known to be dealing with spatial data for most of their daily functions will benefit greatly from GIS, This paper highlights some of the major points.